Atomic Insights into Phase Evolution in Ternary Transition‐Metal Dichalcogenides Nanostructures. Issue 22 (2nd May 2018) - Zou, Yi‐Chao; Chen, Zhi‐Gang; Liu, Shijian; Aso, Kohei; Zhang, Chenxi; Kong, Fantai; Hong, Min; Matsumura, Syo; Cho, Kyeongjae; Zou, Jin
Abstract: Phase engineering through chemical modification can significantly alter the properties of transition‐metal dichalcogenides, and allow the design of many novel electronic, photonic, and optoelectronics devices. The atomic‐scale mechanism underlying such phase engineering is still intensively investigated but elusive. Here, advanced electron microscopy, combined with density functional theory calculations, is used to understand the phase evolution (hexagonal 2H→monoclinic T′→orthorhombic Td ) in chemical vapor deposition grown Mo1− x W x Te2 nanostructures. Atomic‐resolution imaging and electron diffraction indicate that Mo1− x W x Te2 nanostructures have two phases: the pure monoclinic phase in low W‐concentrated (0 < x ≤ 10 at.%) samples, and the dual phase of the monoclinic and orthorhombic in high W‐concentrated (10 < x < 90 at.%) samples. Such phase coexistence exists with coherent interfaces, mediated by a newly uncovered orthorhombic phase Td ′. Td ′, preserves the centrosymmetry of T′ and provides the possible phase transition path for T′→Td with low energy state. This work enriches the atomic‐scale understanding of phase evolution and coexistence in multinary compounds, and paves the way for device applications of new transition‐metal dichalcogenides phases and heterostructures. Abstract : A new orthorhombic Td′ phase is uncovered from chemical vapor deposition grown Mo1− x W x Te2 nanostructures, through atomic‐resolution scanning transmission electron microscopy imaging and density functional theory calculation. Td ʹ preserves the centrosymmetry of monoclinic Tʹ with an energetically favorable structure, allows the lattice‐matched phase coexistence of monoclinic and orthorhombic phases, and provides a possible path for Tʹ–Td transition.